1975
DOI: 10.1530/acta.0.0780001
|View full text |Cite
|
Sign up to set email alerts
|

Lh and FSH in Serum After Intramuscular Administration of Lh/FSH-Releasing Hormone in Normal and Hypogonadal Men

Abstract: The increase in serum concentrations of LH and FSH after intramuscular administration of LH/FSH-RH was investigated in normal and hypogonadotrophic hypogonadal males. LH and FSH were measured by specific radio-immunoassays. To evaluate the appropriate dose of LH/ FSH-RH for intramuscular administration different doses were administered and with 200 μg an increase in LH and FSH was found comparable to the results obtained by other investigators using intravenous administration. After the initial studies a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The serum concentration of both hormones are significantly greater after 14 days of treatment than after 8 days. Although not significantly different we find a tendency to a greater response in LH than in FSH which is in accordance with the results obtained with LH/FSH-RH stimulation of the pituitary gland (Jorgensen et al 1975). …”
Section: Discussionsupporting
confidence: 92%
“…The serum concentration of both hormones are significantly greater after 14 days of treatment than after 8 days. Although not significantly different we find a tendency to a greater response in LH than in FSH which is in accordance with the results obtained with LH/FSH-RH stimulation of the pituitary gland (Jorgensen et al 1975). …”
Section: Discussionsupporting
confidence: 92%
“…In males the oestrogens are derived mostly by peripheral conversion of testosterone (12). The significant correlation found in the present study (8).…”
Section: Discussionsupporting
confidence: 72%
“…In addition to be of potential diagnostic value the gonadotrophin releasing hormone, LH-RH, has also proved to be useful therapeutically in hypogonadal males with hypothalamic dysfunction (2, 8). Mortimer et al (13) demonstrated that 500 Ltg LH-RH administrated subcutaneously three times a day to 12 hypogonadal males increased significantly the serum concentration of LH, FSH, testosterone and dihydrotestosterone.…”
mentioning
confidence: 99%